From Environmental Beliefs to Ecotourism Intention: The Mediating Role of Ecodestination Image in Sustainable Tourism Behavior - Anna Wulandari; Heru Mulyanto; Hamzah Muhammad Mardi Putra; Arief Teguh Nugraha (MASI Mandiri Edukasi, 2026)
Ecotourism has become a key approach to promoting sustainable tourism and environmental conservation, yet the psychological mechanisms driving tourists’ participation remain insufficiently understood. This study addresses this gap by examining how environmental beliefs influence ecotourism intention through the mediating roles of ecodestination image and perceived value among tourists in West Java. A quantitative research design was employed using survey data collected from 280 tourists who had previously visited natural destinations in the region. Data were gathered from an online questionnaire using a bipolar 1–10 scale and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS 3.0. The findings reveal that environmental beliefs significantly influence ecotourism intention both directly and indirectly through ecodestination image. Ecodestination image emerges as a key mediating mechanism, linking internal environmental values to behavioral intention and significantly enhancing perceived value. In contrast, perceived value does not significantly predict ecotourism intention, indicating that environmentally driven psychological factors and destination-related perceptions are more influential than utilitarian evaluations in shaping sustainable travel behavior. These results highlight the critical role of destination-specific perceptions, integrating environmental belief perspectives with tourism marketing constructs. In practice, the study suggests that destination managers should prioritize strengthening the environmental image through sustainability communication and environmental education initiatives. Such strategies can enhance tourists’ pro-environmental attitudes, encourage responsible travel behavior, and support the long-term development of sustainable tourism.